The BNPL phenomenon: Digital consumer communication and behavior in shopee paylater - Ananda, Putri; Pramesthi, Jasmine Alya (Jurnal Kajian Komunikasi, 2025)
Background: Buy Now, Pay Later (BNPL) services experienced 125% growth in Indonesia in 2021-2022. It proves a fundamental transformation in consumer communication and fintech marketing communications, in which the platform’s persuasive architecture and digital word-of-mouth communications shape the financial decisions of the younger generation. Purpose: The study examined consumers’ experiences with Shopee PayLater (SPayLater) through a phenomenological approach, exploring utilitarian-hedonic motivations, impacts on shopping patterns and financial management, users’ subjective experiences, and the socio-psychological factors that influence continued usage behavior. Methods: It employed Interpretative Phenomenological Analysis (IPA) with 20 active SPayLater users. Data were collected through in-depth, semi-structured interviews and digital observations. They were analyzed by integrating the Theory of Planned Behavior, Self-Determination Theory, and Hedonic-Utilitarian motivation theory, with triangulation of methods, sources, and theories. Results: The findings reveal a shift in consumption behavior from “buying by need” to “buying by want,” with peer recommendation more persuasive than formal marketing communication. Implications: The research produces a Digital PayLater Consumer Communication Model (DPCCM) that explains the BNPL communication ecosystem through five components: platform communication strategy, social network influence, individual psychological mechanisms, behavioral consumption manifestation, and feedback loop dynamics. The research provides a significant theoretical contribution to the digital communication literature by producing a new framework for understanding how the dynamics of persuasive communication in the digital commerce ecosystem shape the financial decisions and consumption behavior of Indonesia’s young generation.